PERBEDAAN KEMAMPUAN MOTORIK HALUS ANAK USIA PRASEKOLAH PADA ORANG TUA YANG MENERAPKAN SMART PARENTING DAN TIDAK MENERAPKANSMART PARENTING - Sri Mulyani, Sri Mulyani; Ainu Zuhriyah, Ainu Zuhriyah; Eva Rahayu, Eva Rahayu (Jurnal Penelitian Kesehatan, 2014)
Parents today many of them do not understand about how to properly care for her child or that they could not implement smart parenting , especially in the fine motor development of preschool age children . Where the Smart Parenting is an effort to train , give lessons with the aim of helping to be good and can decide everything correctly . The purpose of this study was to determine differences in fine motor skills in preschool children of parents who apply and do not apply smart parenting smart parenting . In this study, using a type of comparative analytical study with cross-sectional approach . Independent variables of this study were parents who apply smart parenting and parents who do not implement smart parenting . Dependent variable of this study is the fine motor skills of preschool -aged children ( 3-6 years ) . Results reveal that of the 61 respondents implementing smart parenting , the majority of normal children fine motor skills ie 59 respondents and their fine motor skills deviate only 2 respondents . Addition of 27 respondents did not apply smart parenting , the childs fine motor skills are deviated 27 respondents . This suggests there are differences in fine motor skills in children of parents who apply and do not apply smart parenting smart parenting . For that we need the efforts of parents and schools to educate children with smart paradigm . With so children aged 3-6 years to achieve a task that should take place in the golden periodeKeywords : Smart Parenting , fine motor skills Age Preschool